Web Usability of Public Organization Websites: The Case of Indonesian Ministry Websites - Ali Rokhman; Darmanto Sahat Satyawan (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
As a consequence of the development of Information and Communication Technologies (ICT), nowadays almost all governments around the world, included Indonesian government have official websites to provide information and services for their citizen. In the second period of President Susilo Bambang Yudhoyono administration has thirty two ministries and each ministries have an official website. However implementation of the ministry websites have not been measured yet on usability aspect. The objective of this research is to examine the usability of ministry websites of Indonesian Government. Eleven websites was taken as sample in this study. Respondents are 128 Internet users who have competency for assessing web usability. Usability of websites were measured by several indicators were adapted from E-Government Toolkit for Developing Countries that was prepared by the National Informatics Centre and UNESCO. The main indicators consist of navigation architecture, layout design, and content.